(untitled) (قضايا سياسية, 2024)
For almost six decades, the Turkey-Israel relations are deemed solid and strategic due to the mutual interest between both countries. Turkey didn’t only recognize Israel as a state but also it built diplomatic bonds with them. However, although in 1996 their relation was deepened as they signed a strategic agreement, things changed in 2002 when the Justice and Development Party took over Turkey. Besides, the war that Israel launched against Lebanon in 2006 that was also followed by another war against Gaza by the end of 2008. Moreover, the words of the ex-Israeli Prime Minister, Perez, about Gaza war and the altercation with the Turkish President, Erdogan had increased the tension between both countries, the thing that resulted in the Israeli attack on the Freedom Navy in 2010. Therefore, the core objective of this study is to unveil to what extent the takeover of the Justice and Development Party has had an impact on the nature of those countries relations under the local and global changes. Hence, the following questions are aroused: 1) How was the Turkey foreign policy towards Israel from 2010 to 2016? 2) What are the internal and external policies criteria towards Israel? 3) Has their co-operation been affected at the economic, political, the army and even the security level?. The study concluded that the new Turkish policy orientation hasn’t radically changed compared with that before the winning party got inaugurated. More specifically, this orientation is widely explained under the frame of re-positioning and structure, which the party has adopted in the economic, social and political fields. In other words, the fundamentals which are represented in the secularity of the state and which were passed to Turkey by Mustafa Kamal Ataturk would never be touched or ruined. This also includes the conventional relation with Israel since the attitude towards Israel doesn’t merely reflect the Justice and Development Party’s vision, but instead, it reflects the whole country’s vision. This is because everything emanating from the party has to be delivered to the National Security Council of Turkey. Finally, despite the tension in the period of 2010-2016, the Turkey-Israeli relation is deep and cannot easily be abandoned.